Synthesis of well-crystallized Li4Ti5O12 nanoplates for lithium-ion batteries with outstanding rate capability and cycling stability - Sha, Y.; Zhao, B.; Ran, R.; Cai, R.; Shao, Zongping (2013)
As a lithium-intercalation material, high crystallinity is important for Li4Ti5O12 to achieve good capacity and cycling stability, while a large surface area and a short lithium diffusion distance are critical to increase rate capacity. In this study, well-crystallized Li 4Ti5O12 nanoplates with outstanding electrochemical performance were facially prepared through a two-step hydrothermal preparation with benzyl alcohol-NH3·H 2O (BN) as the solvent and a subsequent intermediate-temperature calcination at 500 °C for 2 h in air. To support the superiority of benzyl alcohol-NH3·H2O (BN) for hydrothermal synthesis, ethanol-NH3·H2O (EN) was also comparatively studied as solvent. In addition, different hydrothermal reaction times were tried to locate the optimal reaction time. The nature of as-prepared Li 4Ti5O12-BN (LTO-BN) and Li4Ti 5O12-EN (LTO-EN) was characterized by XRD, N2 adsorption/desorption tests, SEM, TEM and TGA-DSC. Compared with EN, the BN hydrothermal solvent facilitated the formation of nanosheet-Li 4Ti5O12 with wall thicknesses of 8-15 nm and better crystallization. After a 6 h hydrothermal reaction at 180 °C and subsequent calcination, well-crystallized Li4Ti5O 12-BN nanoplates were produced, which demonstrate a superior discharge capacity of 160 mA h g-1, even at 40 C, maintaining a capacity of 88.8% compared with that at 1 C. The nanoplates also exhibited excellent cycling stability, retaining a discharge capacity of 153 mA h g -1 after 1000 charge-discharge cycles at 10 C. © 2013 The Royal Society of Chemistry.